2015
DOI: 10.2135/cropsci2014.04.0310
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Phenotyping of Cotton in Multiple Irrigation Environments

Abstract: Rapid screening of plant growth provides additional phenological information for cotton (Gossypium hirsutum L.), which may then be linked to productivity analysis in breeding and agronomy. We tested automated measurements of plant height, ground cover fraction (GCF), normalized difference vegetation index (NDVI), and canopy temperature (Tc) using a ground‐based platform mounted on a research sprayer on four cotton cultivars (DP1212, DP1219, FM2484, and PHY499) grown under 10 different irrigation levels at Lubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 37 publications
(53 reference statements)
4
54
0
Order By: Relevance
“…2). Further supporting the ability of FB-HTP to monitor plant development under managed stress, Sharma and Ritchie (2015) used a similar system to identify differential growth characteristics among cotton cultivars evaluated under varying irrigation levels. The novel ability of FB-HTP to capture the temporal changes of a phenotype provides the critical pivot needed to focus on developmental quantitative genetics in order to grasp how trait manifestation is a function of many QTL whose effects fluctuate with time (Wu et al, 1999).…”
Section: Plant Canopy Phenotypingmentioning
confidence: 99%
“…2). Further supporting the ability of FB-HTP to monitor plant development under managed stress, Sharma and Ritchie (2015) used a similar system to identify differential growth characteristics among cotton cultivars evaluated under varying irrigation levels. The novel ability of FB-HTP to capture the temporal changes of a phenotype provides the critical pivot needed to focus on developmental quantitative genetics in order to grasp how trait manifestation is a function of many QTL whose effects fluctuate with time (Wu et al, 1999).…”
Section: Plant Canopy Phenotypingmentioning
confidence: 99%
“…These characteristics are useful not only for quantitative analysis of genotype-environment interactions, which is essential for increasing crop performance [3][4][5], but also for improving crop management strategies such as fertilization, irrigation, and optimization of harvesting [6][7][8]. Several studies have shown interactions between geometric parameters of plants and crop yield as well as biomass [3,5,[9][10][11]. Manual measurements of crop traits, which are still often used in practical phenomic applications, have significant limitations and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Manual measurements of crop traits, which are still often used in practical phenomic applications, have significant limitations and drawbacks. These methods are time-consuming and labor intensive, which inevitably increases cost [9,12]. Additionally, manually obtained measurements are subject to human error due to fatigue and distractions during data collection.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation indices have been primarily used to indicate the response of vegetative growth to biotic and abiotic stresses of several crops, including cotton (Falkenberg et al, 2007; Zhao et al, 2007; Sharma and Ritchie, 2015). However, the use of these indices to determine phenology of the crop have been limited by the inability of the sensors to specifically detect flowers and bolls on the plants.…”
mentioning
confidence: 99%